The Need for Pediatric Formulations to Treat Children with HIV - Adrienne F. Schlatter; Andrew R. Deathe; Rachel C. Vreeman (AIDS Research and Treatment)
Over 3.2 million children worldwide are infected with HIV, but only 24% of these children receive antiretroviral therapy (ART). ART adherence among children is a crucial part of managing human-immunodeficiency virus (HIV) infection and extending the life and health of infected children. Important causes of poor adherence are formulation- and regimen-specific properties, including poor palatability, large pill burden, short dosing intervals, and the complex storage and transportation of drugs. This review aims to summarize the various regimen- and formulation-based barriers to ART adherence among children to support the need for new and innovative pediatric formulations for antiretroviral therapy (ART). Detailing the arguments both for and against investing in the development of pediatric HIV medications, as well as highlighting recent advances in pediatric ART formulation research, provides a synopsis of the current data related to pediatric ART formulations and adherence.